Levels of comprehension when reading informational texts in different media - Lemos, Keyla Maria Frota (2024)
This research was developed to investigate the levels of understanding of information in academic and journalistic texts read in different digital media and in print, in order to check if there would be significant differences in reading in these media. The study was based on Kintsch e Rawson’s (2013) comprehension model and used Barret’s (1968) taxonomy, and its adaptation, in the elaboration of the reading tests. It is a quasi-quantitative research, conducted with 24 participants, which involved reading texts and carrying out comprehension tests, in order to assess how much readers understood information in the texts read, two academic (an abstract and an introduction of scientific articles) and two journalist texts (academic news and journalistic news) when read in different digital media (cell phone, tablet and computer) and in print. Statistical tests (ANOVA and t test) did not identify significant differences in comprehension in relation to the text read or the media used for reading. Although the results did not reveal that digital reading can hinder – or benefit – comprehension of informative texts when read academic and journalistic texts, further inquiry is needed so we can achieve conclusive results. Keywords: Levels of reading comprehension; Reading in different media; Informative texts.